The coming harmonization of climate change policy and international investment law - Daniel M. Firger (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
The author examines recent trends in international climate finance and foreign direct investment to identify connections, and potential areas of harmonization, between the two regimes. On the one hand, international climate policy is emphasizing the growing role of private sector investment in clean energy and sustainable development. On the other hand, international investment law is changing to take account of social and environmental goals, including climate mitigation.
Keywords: 330